Fate of fumonisins in cattle fed contaminated feed - Thakur, R.A.; Wallace, N.; Smith, J. Scott; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fumonisins are water-soluble carcinogenic mycotoxins produced by many species of Fusarium molds. Fumonisins occur widely in corn, making them a problem in corn-based feed. Their toxicity has been established in many species. However, their effects on cattle and the potential of carryover to the human diet through beef has not been studied extensively. A 30-day cattle feeding study was conducted by feeding fumonisin-contaminated corn grits dosed at 400 g/g fumonisin B1 (FB1) and 130 g/g fumonisin B2 (FB2) to 3 steers averaging 480 lb. Premortem analysis involved urinalysis; tests for liver functionality; and analysis of the blood, urine, and feces for the presence of fumonisins or their metabolites. Postmortem analysis involved necropsy, analysis of tissue for fumonisins, and histopathology. The test animals showed some s light liver abnormalities. The feces contained unmetabolized FB1 and FB2 ($80% of the fed dose), and trace amounts were detected in the urine. Tissue analysis resulted in detection of 2.1 g/g FB 1 in the liver, 0.1 g/g FB1 in the muscle, and 0.02 g/g FB1 in the kidney, indicating a high feed:tissue ratio, and consequently insignificant carryover into the human diet.
Keywords: Beef; Fumonisins; Toxicity; Residues in tissues